STRATEGI PEMBELAJARAN SENI BUDAYA (MUSIK) DI SMA NEGERI 10 PADANG - Fidrianti, Syahrani; Ardipal (Universitas Negeri Padang, 2025)
This study aims to uncover and describe the strategies used in Arts and Culture learning at SMA Negeri 10 Padang. The method used is qualitative with a descriptive approach. Data collection was conducted through observation, interviews, and documentation. The research instrument was the researcher herself and assisted by supporting instruments such as a cellphone camera, a cellphone voice recorder, stationery and notebooks. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that Arts and Culture teachers at SMA Negeri 10 Padang apply several learning strategies, including indirect instruction, interactive instruction, and cooperative learning. The strategies implemented have encouraged active participation, creativity, and student confidence, although improvements in facilities and teacher competency are still needed.